PENGARUH KUALITAS KEPEMIMPINAN, KONFLIK PEKERJAAN KELUARGA, DAN DUKUNGAN SOSIAL TERHADAP PRESENTEEISM DENGAN BURNOUT SEBAGAI VARIABEL INTERVERNING (Studi Pada Dinas Kependudukan dan Pencatatan Sipil Kota Semarang) - Handoko, Priyo Adhi; Yuniawan, Ahyar (Diponegoro Journal of Management, 2017)
The purpose of this study was to examine the effect of leadership quality, work family conflict, and social support to presenteeism with burnout as intervening variable. This research was conducted at Agency of Population and Civil Registration Semarang City, with sample size was 80 employees who have married status with sampling technique using total sampling. The analysis used included multiple linear regression analysis, path analysis and test of sobel to test mediation effect.The results show a positive and significant relationship between: a) leadership quality with presenteeism, b) work family conflict with presenteeism, c) social support with presenteeism, d) leadership quality with burnout, e) work family conflict with burnout, f) social support with burnout, g) burnout with presenteeism. The results of this study also show that burnout proved to be a mediating variable between leadership qualities, work family conflict, and social support for presenteeism.